A computational agent model for stress reaction in natural disaster victims - Mohammed, Hayder; Ab. Aziz, Azizi; Che Pa, Noraziah; Mohd Shabli, Ahmad Hanis; Abu Bakar, Juliana Aida; Alwi, Asmidah (2016)
Computational model of stress reaction among natural disaster victim can be of interest for different purposes, varying from the study of virtual human cognition behaviours in stressful events to the development of intelligent support for cognitive therapies.This paper presents a novel computational agent model of stress reaction among natural disaster victims.Simulation experiments under different conditions and parameters setting pointed out that the model is able to produce realistic behaviour of different types of personalities.Moreover, by a mathematical analysis the equilibria of the model have been determined, and by automated trace checking, a number of selected cases from the literatures have been internally validated.